MiR-2 family regulates insect metamorphosis by controlling the juvenile hormone signaling pathway. - Fernández-Lozano, Jesús; Montañez, Raúl; Bellés, Xavier (National Academy of Sciences, 2015)
In 2009 we reported that depletion of Dicer-1, the enzyme that catalyzes the final step of miRNA biosynthesis, prevents metamorphosis in Blattella germanica. However, the precise regulatory roles of miRNAs in the process have remained elusive. In the present work, we have observed that Dicer-1 depletion results in an increase of mRNA levels of Krüppel homolog 1 (Kr-h1), a juvenile hormone-dependent transcription factor that represses metamorphosis, and that depletion of Kr-h1 expression in Dicer-1 knockdown individuals rescues metamorphosis. We have also found that the 3′UTR of Kr-h1 mRNA contains a functional binding site for miR-2 family miRNAs (for miR-2, miR-13a, and miR-13b). These data suggest that metamorphosis impairment caused by Dicer-1 and miRNA depletion is due to a deregulation of Kr-h1 expression and that this deregulation is derived from a deficiency of miR-2 miRNAs. We corroborated this by treating the last nymphal instar of B. germanica with an miR-2 inhibitor, which impaired metamorphosis, and by treating Dicer-1-depleted individuals with an miR-2 mimic to allow nymphal-to-adult metamorphosis to proceed. Taken together, the data indicate that miR-2 miRNAs scavenge Kr-h1 transcripts when the transition from nymph to adult should be taking place, thus crucially contributing to the correct culmination of metamorphosis.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/10338 y https://www.pnas.org/author-center/publication-charges#:~:text=All%20PNAS%20articles%20are%20free,PubMed%20Central%20for%20the%20authors.
Keywords: Insectos - Metamorfosis; MicroARNs; Algorithms; miRNAs; Metamorphosis; Evolution; Insects